Impact of a nurse-led intervention to improve screening for cardiovascular risk factors in people with severe mental illnesses. Phase-two cluster randomised feasibility trial of community mental health teams - Nazareth Irwin; Osborn David PJ; Wright Christine A; King Michael B (BMC, 2010)
Abstract Background People with severe mental illnesses (SMI) are at increased risk of cardiovascular disease (CVD). Clinical guidelines recommend regular screening for CVD risk factors. We evaluated a nurse led intervention to improve screening rates across the primary-secondary care interface. Methods Six community mental health teams (CMHTs) were randomised to receive either the nurse led intervention plus education pack (n = 3) or education pack only (n = 3). Intervention (6 months): The nurse promoted CVD screening in primary care and then in CMHTs. Patients who remained unscreened were offered screening by the nurse. After the intervention participants with SMI were recruited from each CMHT to collect outcome data. Main outcome: Numbers screened during the six months, confirmed in General Practice notes. Results All six CMHTs approached agreed to randomisation. 121 people with SMI participated in outcome interviews during two waves of recruitment (intervention arm n = 59, control arm n = 62). Participants from both arms of the trial had similar demographic profiles and rates of previous CVD screening in the previous year, with less than 20% having been screened for each risk factor. After the trial, CVD screening had increased in both arms but participants from the intervention arm were significantly more likely to have received screening for blood pressure (96% vs 68%; adjusted Odds Ratio (OR) 13.6; 95% CI: 3.5-38.4), cholesterol (66.7% vs 26.9%, OR 6.1; 3.2-11.5), glucose (66.7% vs 36.5% OR 4.4; 2.7-7.1), BMI (92.5% vs 65.2% OR 6.5; 2.1-19.6), and smoking status (88.2% vs 57.8% OR 5.5; 3.2-9.5) and have a 10 year CVD risk score calculated (38.2% vs 10.9%) OR 5.2 1.8-15.3). Within the intervention arm approximately half the screening was performed in general practice and half by the trial nurse. Conclusions The nurse-led intervention was superior, resulting in an absolute increase of approximately 30% more people with SMI receiving screening for each CVD risk factor. The feasibility of the trial was confirmed in terms of CMHT recruitment and the intervention, but the response rate for outcome collection was disappointing; possibly a result of the cluster design. The trial was not large or long enough to detect changes in risk factors. Trial Registration International Standard Randomised Controlled Trial Registration Number (ISRCTRN) 58625025.